Creating utilitarian and hedonic Purchasing Values on satisfaction and loyalty to Shopping Centers (case study: shiraz hyperstar) - Masoud Birjandi; Abdolkhalegh Gholami; Mohammad Haghighi (مطالعات مدیریت راهبردی, 2018)
Investigating the factors that affect consumers' satisfaction and loyalty leads to a deep understanding  of consumer behavior that enables marketers to deliver products and services in accordance with the needs of consumers in the market. The purpose of this study is to examine the effect of dimensions Shopping values ​​are on customer satisfaction and loyalty. The statistical population of this research is customers of Hyperstar shopping center in Shiraz. Simple random sampling and sample size are 447 people. The data gathering tool was a questionnaire. For data analysis, structural equation modeling and SmartPls software have been used. The results of the research show that in the Hyperstar, two variables of utilitarian value and hedonic value of direct effect, and the variables of money saving, breadth of choice, convenience in purchasing, exploration, spatial attachment, social position have indirect impact on customer satisfaction and loyalty. Also, the impact of custom product variables and entertainment on customer satisfaction and loyalty has not been confirmed. In addition, the effect of satisfaction on customer loyalty has been confirmed.